Determination of Parabens in Polish River and Lake Water as a Function of Season. (23rd July 2016) - Zgoła-Grześkowiak, Agnieszka; Jeszka-Skowron, Magdalena; Czarczyńska-Goślińska, Beata; Grześkowiak, Tomasz
ABSTRACT: A method for the determination of methylparaben, ethylparaben, propylparaben, butylparaben, and benzylparaben is reported. A polymeric cartridge containing ultra-pure polystyrene cross-linked with 50% divinylbenzene and 50% poly(methyl methacrylate) was employed for the isolation of parabens from water samples. The extracted samples were analyzed by high-performance liquid chromatography coupled with tandem mass spectrometry. The limits of detection for the method were from 0.3 to 2.9 ng L −1 that allowed the determination of parabens in river and lake water samples with suitable precision and accuracy. There was high variability in the results depending on time of sample collection. The highest concentrations were obtained for samples collected in July – up to 466 ng L −1 of methylparaben and 144 ng L −1 of propylparaben.